Measuring performance directly using the veterans health administration electronic medical record: a comparison with external peer review. - Goulet, Joseph L; Erdos, Joseph; Kancir, Sue; Levin, Forrest L; Wright, Steven M; Daniels, Stanlie M; Nilan, Lynnette; Justice, Amy C (Medical care, 2007)
Electronic medical records systems (EMR) contain many directly analyzable data fields that may reduce the need for extensive chart review, thus allowing for performance measures to be assessed on a larger proportion of patients in care.
Keywords: Aged; Blood Pressure; Cholesterol, LDL; Cross-Sectional Studies; Delivery of Health Care; Female; Hemoglobin A, Glycosylated; Humans; Male; Medical Records Systems, Computerized; Peer Review; Quality of Health Care; Task Performance and Analysis; United States; United States Department of Veterans Affairs